Hubungan Dukungan Keluarga Terhadap Manajemen Laktasi Pada Ibu Bekerja: The Relationship of Family Support to the Management of Lactation in Working Mothers - Arlia Purwaningsih; Oswati Hasanah; Wasisto Utomo (Fakultas Keperawatan Universitas Andalas, 2013)
The purpose of this research was to determine the relationship between family support and lactation management among working mothers. This research was a descriptive correlation with cross sectional approach, conducted among 35 working mothers who work as a nurse in Arifin Achmad Hospital in Pekanbaru taken with total sampling. A set of valid and reliable questionnaire used to collect the data. The results showed a weak positive correlation in different direction between family support and lactation management (r= 0.295), with P value= 0,086 (> 0,05), this resulst indicates that there was no significant correlation between two variable. This result suggest a nurse as a working mother to improve their social environment while breastfeeding to motivate, persuade, and support them on performing optimal lactation management.